Clinical characteristics, treatment and outcomes of acute propanil poisoning in a 7-year retrospective cohort study - Panee Rittilert; Charuwan Sriapha; Achara Tongpoo; Aim-On Pradoo; Winai Wananukul; Satariya Trakulsrichai (Toxicology Reports, 2022)
The present study was a 7-year retrospective cohort study (2012–2018) of patients treated for acute propanil poisoning by ingestion, using data from Ramathibodi Poison Center, Thailand. The aim of this study was to describe the clinical characteristics, treatment, outcomes and factors associated with moderate to severe outcomes and death following acute exposure to propanil. The effect of administering multiple-dose activated charcoal (MDAC) on clinical outcomes was also evaluated. A total of 275 cases were included. The results show that two thirds of patients were male and mean age was 40 years. Patients ingested either propanil or a mixture of propanil and other herbicides. The majority (98%) of exposures was intentional. Most patients (65.5%) presented with gastrointestinal symptoms. Methemoglobinemia and hemolysis were observed in 108 patients (39.3%) and 25 patients (9.1%), respectively. Median time to onset of methemoglobinemia and hemolysis after propanil ingestion was 5.5 and 48 h, respectively. One hundred and forty-one patients (51.3%) were treated with MDAC, and some patients received methylene blue (21.5%), intubation (18.5%), or blood transfusions (8%). All patients were admitted to hospitals. The median length of hospital stay of patients who survived was 3 days. Multivariate analysis indicated that neurological symptoms at presentation, methemoglobinemia and acute kidney injury during admission, were associated with moderate to severe outcomes. Factors associated with mortality were older age, larger amount of ingestion, neurological symptoms at presentation and hypotension during admission. The overall mortality rate was 6.2%. The mortality rate was 3.6% in patients that received MDAC and 9% in patients that did not, although the difference was not statistically significant. Subgroup analysis of patients who developed methemoglobinemia or both methemoglobinemia and hemolysis found a statistically significant lower mortality rate in patients that received MDAC. In conclusion, methemoglobinemia and hemolysis contribute to poor outcomes in acute propanil poisoning. Age, amount of ingestion, neurological symptoms at presentation and hypotension during admission could prognosticate deaths, and patients with these factors should be closely observed and aggressively managed.